Actas Alexander: La elaboración de la información (ING) - Dörries, Esteban (2004)
To compare the obtained data of the “Actas Alexander” with the present situation, it was necessary to design and calculate a crossed GPS measurement along the pegged limits of the northern border. The transformation of coordinates in diverse variants, next to other criteria, allowed to make the comparative study of border landmarks.